2016
DOI: 10.1038/srep25873
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-dependent RNA polymerase gene in bat genomes derived from an ancient negative-strand RNA virus

Abstract: Endogenous bornavirus-like L (EBLL) elements are inheritable sequences derived from ancient bornavirus L genes that encode a viral RNA-dependent RNA polymerase (RdRp) in many eukaryotic genomes. Here, we demonstrate that bats of the genus Eptesicus have preserved for more than 11.8 million years an EBLL element named eEBLL-1, which has an intact open reading frame of 1,718 codons. The eEBLL-1 coding sequence revealed that functional motifs essential for mononegaviral RdRp activity are well conserved in the EBL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 47 publications
(68 reference statements)
1
47
2
Order By: Relevance
“…The cells are robust and easy to passage. In addition, eEBLL-1 is present in the genome of HAMOI-EnK cells, which retains a large and intact ORF as previously reported [6]. Furthermore, we demonstrated the presence of sense-oriented eEBLL-1 transcripts in the cells.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…The cells are robust and easy to passage. In addition, eEBLL-1 is present in the genome of HAMOI-EnK cells, which retains a large and intact ORF as previously reported [6]. Furthermore, we demonstrated the presence of sense-oriented eEBLL-1 transcripts in the cells.…”
supporting
confidence: 86%
“…Although we demonstrated that eEBLL-1 is present in the genome of E. nilssonii in the previous study [6], eEBLL-1 might have been lost during long-term passage. Thus, we performed genomic PCR to detect eEBLL-1 in the genome (PCR conditions are available in Supporting information).…”
contrasting
confidence: 61%
See 3 more Smart Citations